1992
DOI: 10.1007/bf00115403
|View full text |Cite
|
Sign up to set email alerts
|

Origins of atmospheric particulate matter over the North Sea and the Atlantic Ocean

Abstract: During the ANT Vll/l cruise of the RV Polarstern from Bremerhaven (Germany) to Rio Grande do Sul (Brazil), atmospheric particulate matter was collected by bulk filtration with a time step of 36 hours. Elemental analyses were performed in order to determine atmospheric aerosol concentrations of Al, Si, P, S, K, Ca, Ti, Mn, Fe, and Zn over the North Sea, the Channel, and the North and South Atlantic. The slight and continuous moving in latitude, associated with the large variability in concentration levels and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
2
16
0
1
Order By: Relevance
“…Coarse phosphorus, an element emitted during plant guttation and transpiration [ Artaxo and Hansson , 1995], accounted for less than 1% of the dust mass (coarse P/Al = 0.007 (Table 4); dust mass = Al/0.0813 [ Mason , 1966]). The SHADE P/Al ratio is consistent with the value of 0.0086 measured by Losno et al [1992]. These facts suggest that organic material is minimal in Saharan dust.…”
Section: Resultssupporting
confidence: 87%
“…Coarse phosphorus, an element emitted during plant guttation and transpiration [ Artaxo and Hansson , 1995], accounted for less than 1% of the dust mass (coarse P/Al = 0.007 (Table 4); dust mass = Al/0.0813 [ Mason , 1966]). The SHADE P/Al ratio is consistent with the value of 0.0086 measured by Losno et al [1992]. These facts suggest that organic material is minimal in Saharan dust.…”
Section: Resultssupporting
confidence: 87%
“…Finally, Miami and Barbados are not strongly affected by biomass burning during the summer when most of the samples were taken. In some other regions, such as sub-Saharan Africa, the relationship between dust and TP may be masked by high levels of biomass burning and lower levels of dust [Baker et al, 2006b;Losno et al, 1992]. The biomass burning samples at our sites provided much less TP (169 AE 142 pmol m À3 ) than the dust days (651 AE 249 pmol m À3 ).…”
Section: Resultsmentioning
confidence: 79%
“…Our median trace metal concentration data (Tables and ) and their ranges (Figure ) are consistent with previous ship‐board studies in the Atlantic, although there is a high degree of variability in observed trace metal concentrations in all of these data. For example, total and soluble Fe concentrations have been reported in the range 1.4–134,000 pmol m −3 [ Völkening and Heumann , ; Losno et al ., ; Rädlein and Heumann , , ; Johansen et al ., ; Chen and Siefert , ; Baker et al ., ; Buck et al ., ] and <2.0–775 pmol m −3 [ Johansen et al ., ; Chen and Siefert , ; Baker et al ., ; Buck et al ., ], respectively. In Tables S6 and S7, we list examples of, respectively, total and soluble aerosol trace metal concentrations previously reported for our five deposition regions.…”
Section: Resultsmentioning
confidence: 99%